2021
DOI: 10.3389/fpsyg.2021.678513
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 Crisis as a Teachable Moment for Lifestyle Change in Dutch Cardiovascular Disease Patients

Abstract: Objective: When lifestyle changes are needed, life events or crises such as COVID-19 may function as “teachable moments”. This study aimed to explore whether the pandemic can provoke a teachable moment regarding lifestyle change in cardiovascular disease patients.Method: In this cross-sectional survey study, 830 cardiovascular disease patients reported their intentions to change lifestyle, instigated by the corona crisis, together with risk perception, affective impact, and changed self-concept, based on a “te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 44 publications
2
6
0
1
Order By: Relevance
“…Someone’s health behaviors can thus be influenced by an assessment of the importance of social roles to a person ( Stets, 2020 ). We also found evidence for this phenomenon in the high association between Changed self-concept and Event-related lifestyle change in the current study, as well as in our previous work ( Brust et al, 2021 ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Someone’s health behaviors can thus be influenced by an assessment of the importance of social roles to a person ( Stets, 2020 ). We also found evidence for this phenomenon in the high association between Changed self-concept and Event-related lifestyle change in the current study, as well as in our previous work ( Brust et al, 2021 ).…”
Section: Discussionsupporting
confidence: 91%
“…The KMO (0.84) and significant Bartlett’s test of sphericity (χ2(1378, N = 300) = 6617;p < 0.001) indicated that data from the first half of the dataset were acceptable for factor analysis ( Watkins, 2018 ). Next, seventeen items ( McBride et al, 2003 , Lawson and Flocke, 2009 , Brust et al, 2021 , Karvinen et al, 2015 , Kim, 2013 , Watkins, 2018 , Bandura, 1998 , Stets, 2020 , Becker, 1974 , Olson, 2010 , Nagy et al, 2017 , Lt and Bentler, 1999 , Kline, 2015 , Cohen, 1988 , Fotuhi et al, 2013 , Chiou and Wan, 2007 , Oliveira et al, 2019 ) were removed from the dataset because they consistently showed communities below < 0.30, indicating that they possibly not load sufficiently on any factor. The new EFA showed that nine factors had eigenvalues over Kaiser’s criterion 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that the COVID-19 pandemic provides an opportunity for healthcare professionals to promote lifestyle change ( 43 , 44 ). When regarding dementia risk, the general population is mostly unaware of its relation with lifestyle ( 45 , 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Described as an event or circumstance that motivates an individual to take positive actions regarding their health, ‘teachable moments’ have been examined across an array of settings over the years to assess whether health events can motivate risk‐reducing behaviours. For example, HIV treatment initiation and smoking cessation (Vidrine et al, 2018 ), antenatal care visits and screening for sickle cell and thalassemia (Brown et al, 2011 ; Tsianakas et al, 2012 ), COVID‐19 crisis and lifestyle change in cardiovascular disease patients (Brust et al, 2021 ), ‘cancer worry’ and smoking cessation (McBride et al, 2008 ) and cancer screening, diagnosis, care and survivorship (Gray et al, 2021 ; Karvinen et al, 2015 ; Kathuria et al, 2020 ; McBride et al, 2017 ; Neumann et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%